Definition in testing for the probability of exit of the aircraft in informational contact with air objects - S. V. Nikolaev; A. A. Tikhonov; D. S. Merencov (Научный вестник МГТУ ГА, 2018)
The article presents a methodology for determining the probability of aircraft information contacting airborne objects within flight test procedures. The methodology is based on the experimental-theoretical test method, based on the application of mathematical modeling. The technique differs from the known ones in that it uses modern information technologies, and the adopted mathematical model is implemented in the form of a computer program. In addition, detecting the given performance indicator in flight experiments is inappropriate because of significant resource costs. This technique is suitable for practical testing purposes and allows determining the aircraft efficiency index when searching air objects – the probability of an information contact with a typical air facility. The presented computer program provides the performance of calculations of the output index for different values and combinations of factors influencing the result. The simulation was performed and the probabilities of the aircraft information contact with typical airborne objects under given conditions were obtained. The results of the influence research on the probability of groups of factors outlet into information contact: the aircraft and the air object characteristics, the quality of the initial information about it, search conditions are presented. As a result of the work, the main regularities are established when solving the problem of the aircraft information contact with an air object. The computer program created within the methodology framework has a modern graphical interface and allows reducing the time spent by the researcher on the processing of test results. The developed technique allows performing a comparative assessment of the aircraft capabilities to detect airborne objects in tests.